Formulation and Evaluation of Glimepiride Cordia dichotoma G. Forst Fruit Mucilage Sustained Release Matrix Tablets - Abdul Ahad, Hindustan; Kiranmaye, N.; Haripriya, H.; Ruksana, H.; Madhu Babu, B. (Asian Journal of Chemistry, 2010)
The main aim of the present investigation is to develop a sustained release matrix tablets of glimepiride with Cordia dichotoma G. Forst fruit mucilage and to study its functionality as a matrix forming agent for sustained release. Physico-chemical properties of dried powdered Cordia dichotoma G. Forst fruit mucilage were studied. Various formulations of glimepiride Cordia dichotoma G. Forst mucilage (CD-1, CD-2, CD-3, CD-4 and CD-5) were prepared. They found to have better uniformity of weight and drug content with low SD values. The swelling behaviour and release rate characteristics were studied. The dissolution study proved that the dried Cordia dichotoma G. Forst fruit mucilage can be used as a matrix forming material for making sustained release tablets.